Development of Malaysian Sign Language (MSL) Mobile Apps - Lim, Yun Chao; Tukiran, Zarina (Evolution in Electrical and Electronic Engineering, 2025)
This work describes the development of a Malaysian Sign Language (MSL) mobile application to bridge the communication gap between the deaf and hard-of-hearing people in Malaysia. The motivation for this work stems from the lack of Malaysian Sign Language (MSL) learning resources, especially among the general public. The application is developed using Flutter on the Android platform. It contains topic-based video tutorials, interactive quizzes, and MSL vocabulary translation functions. A preliminary survey of college students aged 18-24 showed that 86.7% of the respondents had never used sign language. In contrast, 86.7% of the respondents showed a strong interest in learning sign language. Test results showed that the stability of the application reached 90%, and 100% of users reported that they did not encounter accessibility issues, which proves its effectiveness and inclusiveness. In addition, 66.7% of users were satisfied with the feature. Offline access, multi-language support, social features, and personalisation options will be further enhanced to improve the user experience and promote the broader application of Malaysian Sign Language education.